Mount Agung; The Beauty and The Mighty - Putu Herry Hermawan Priantara (Bali Tourism Journal, 2017)
Mount Agung is the highest mountain in Bali. Located on Karangasem regency, this most elevated point in the island of Gods is sacred by the Balinese and becomes center of spiritual activities on the island. Mount Agung is an active stratovolcano. Some local volcanic and tectonic earthquakes have been reported on August 10th, 2017. as a result, The locals who live within 9 - 12 km zone from the crater have been secured. Mount Agung’s condition is fluctuate, after BNPB lowered its status from level IV to III, and the refugee went home, the volcano experienced phreatic eruption then followed by magmatic eruption on late November 2017. the news about mount Agung’s activities made tourists afraid to visit Bali. It is proved by declining number of tourist visit Bali. The government through related agencies explain that it is still possible to visit Bali. However, they should avoid any activities in the disaster-prone area. Besides, it is being discussed about plans to make the eruption as a tourist attraction. The program aims to offer new tourism potentials. Thus it may elevate the number of tourist visits to Bali as well as provide employment opportunities for the refugees.